YOSERIZAL: PERANANNYA DALAM PENDIDIKAN ISLAM DI SALIDO KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN (2000-2010) - Dewi, Gita Asmara (Pendidikan Sejarah, 2014)
This research discusses about Yoserizal; Role of Islamic Department at Salido Kec. IV Jurai Kabupaten Pesisir Selatan (2000-2010). Writing is done because Yoserizal has big role in advance of Islamic education at Salido. The case is started from condition of children at Salido that does not have education and does not understand about religion. So, Yoserizal want to build free school and teach religion knowledge. Many challenges is building free school until now he success building Pesantren Al-Kasyaf that almost has three hundred person which come many countries at Sumatera Barat. The purpose of the research is to describe autobiography and family field Yoserizal in Islamic Education at Salido Kec. IV Jurai. The method that is used in the research is history method with heuristic (data collection), source critic, and showing the fact into general history writing that is called historiography. The result of the research shows that travel of Yoserizal from start until build the Pesantren Al-Kasyaf is not easy and many challenge happen that start from unlike society to him toward what he do. But he still patience, hope, and hard work, so Yoserizal success what he hope and give the information to society about the real religion. Now, Pesantren Al-Kasyaf gets appreciation and support from other part, because it can help children which not able to continue their education. Yoserizal give free to children from first enter until pass graduated. Based the result of research, it can be concluded that action of Yoserizal in Islamic Education at Salido is done toward some ways like building Pesantren Al-Kasyaf, following Islamic Organization and doing Islamiah Daqwah Program.